Tantangan Peradilan Adat Laot di Aceh - Teuku Muttaqin Mansur (Universitas Syiah Kuala, 2012)
ABSTRACT: The presence of the commander Laot Laot and customary law is recognized in national legal systems. One is owned by the authority to settle the dispute through traditional justice. So far, the customary judicial decision Laot followed. But viewed from the provisions of national law, customary judicial decision Laot does not have a strong legal basis. This research is descriptive analytical, normative juridical approach sociological and juridical. From the research note that the judiciary can enforce the law and all courts established by state law, not including the customary judicial Laot in it. This judicial decision can only provide a peaceful because the decision is relative or voluntary. Parties who are not satisfied, opened the opportunity to reopen the law through the state courts. The Challenge of Customary Justice of The Sea